Solely lung-involved IgG4-related disease : a case report and review of the literature - Zhang, Xiao-Qin; Chen, Guo-Ping; Wu, Sheng-Chang; Yu, Sa; Wang, Hong; Chen, Xuan-Yi; Ren, Zhuo-Chao (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
By analyzing the clinical data of 1 case of IgG4-related lung disease(IgG4-RLD) and the review of literature, the author investigated the clinical characteristics of IgG4-RLD. IgG4-RLD is a rare disease characterized by significant elevation of serum IgG4 and infiltration of a large number of IgG4+ plasma cells. The clinical manifestations of the disease were nonspecific, and the imaging features were mixed with several types. The disease can only be involved in the lung, but also multiple organ involvement. Solely lung-involved IgG4-RD is not only extremely rare but also easily misdiagnosed as tuberculosis, lung cancer, lymphoma and other common pulmonary diseases. Histopathological examination is the key to the diagnosis of the disease. Corticosteroids are the first choice of treatment, and the overall prognosis is good.